Optimal sourcing orders under supply disruptions and the strategic use of buffer suppliers - Sarah Parlane; Ying-Yi Tsai (University College Dublin, UCD School of Economics, 2014)
This paper analyses procurement from two, risk-averse, suppliers who are responsible for the timely delivery of some inputs. Their production is subject to inherent disruptions. We characterize the optimal contracts when suppliers can invest to lower the risk of delays that are costly to the manufacturer. When investment is contractible, we show that issuing asymmetric contracts, whereby the buyer is more heavily dependent on one supplier, is optimal as the cost associated with supply disruptions increases. When investment is not contractible, we show that large orders can be used as an incentive devise. Thus, the strategy consisting of selecting one supplier as a main producer and another as a buffer has further desirable advantages under moral hazard.
Keywords: D23; D86; L24; 330; Investment; Risk; Costly Delays; Order Size and Moral Hazard